2010
DOI: 10.1136/jcp.2009.070649
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyoma of the gallbladder: a case report with review of the literature and discussion of the differential diagnosis: Figure 1

Abstract: Mesenchymal neoplasms of the gallbladder are rare, and most represent sarcomas of various histological types. To our knowledge, only a few patients with multiple Epstein-Barr virus (EBV)-associated smooth muscle tumours of the gallbladder in the setting of immunodeficiency have been reported in the English literature, but no single case of conventional leiomyoma has been well documented to date. A case of gallbladder leiomyoma in a healthy 34-year-old woman is described here. The tumour was found incidentally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…Leiomyoma of the gallbladder has been previously reported in one dog, 10 and a few case reports have been published in humans. 22,23,24 Gallbladder lymphoma was found in one dog in our study, and has been reported in single case reports in the dog 25 and cat. 26 This has also been a reported gallbladder neoplasm in humans.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Leiomyoma of the gallbladder has been previously reported in one dog, 10 and a few case reports have been published in humans. 22,23,24 Gallbladder lymphoma was found in one dog in our study, and has been reported in single case reports in the dog 25 and cat. 26 This has also been a reported gallbladder neoplasm in humans.…”
Section: Discussionsupporting
confidence: 77%
“…Leiomyoma was the next most common primary gallbladder neoplasm in our study, constituting three of the 15 (20%) cases. Leiomyoma of the gallbladder has been previously reported in one dog, 10 and a few case reports have been published in humans 22,23,24 . Gallbladder lymphoma was found in one dog in our study, and has been reported in single case reports in the dog 25 and cat 26 .…”
Section: Discussionsupporting
confidence: 65%
“…Wachter et al first reported a case of leiomyoma of the gallbladder in 2010 (3). The present case is unique since the patient had multiple metastatic GISTs in the liver, and the gallbladder nodule was preoperatively suspected to be metastatic GIST.…”
Section: Discussionmentioning
confidence: 83%
“…Benign mesenchymal tumors of the gallbladder are extremely rare, but granular cell tumor is the most common type of benign mesenchymal tumor (2). Leiomyoma is one of the common mesenchymal tumors of the gastrointestinal tract, particularly in the esophagus and colon; however, only one case of leiomyoma of the gallbladder has been reported in the English-language literature (3). In this case report, we describe a second case of leiomyoma of the gallbladder in a patient with metastatic gastrointestinal stromal tumors (GISTs) in the liver and discuss the differential diagnostic considerations.…”
Section: Introductionmentioning
confidence: 90%
“…Microscopic smooth muscle fibers with a fascicular pattern with eosinophilic cytoplasm and an elongated nucleus are observed microscopically. Immunohistochemically, the smooth muscle differentiation markers expressed are SMA, desmin, and h-Caldesmon, and are commonly negative for CD34, CD117, and S100 [1]. In a study carried out in Chile by Torres-Q [2] 5,699 biopsies were evaluated from 1998 to 2007, of which 4.9% reported benign tumor lesions, the most frequent being gallbladder polyp (45.5%) and an only one case of leiomyoma was found (0.4%) [2].…”
Section: Discussionmentioning
confidence: 99%